Steel material joined body and manufacturing method thereof

By aligning the central axes of steel materials with different diameters and maintaining a specific carbon concentration with a concentration gradient layer at the joining interface, the bending strength of steel joints is significantly improved.

JP2025063345APending Publication Date: 2025-04-16NETUREN CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2023172402
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-10-04
Publication Date
2025-04-16

AI Technical Summary

Technical Problem

Existing steel joints with different diameters of joint surfaces lack improved bending strength, as the central axes of the joined surfaces do not coincide, and the carbon concentration at the joining interface is not optimized.

Method used

A steel joint is created where the central axes of the bonding surfaces of steel materials with different diameters coincide, and the carbon concentration at the joining interface is maintained between 0.20 mass% and 2.10 mass% with a concentration gradient layer that decreases carbon concentration away from the interface.

Benefits of technology

This approach enhances the bending strength of steel joints with different diameters by optimizing the carbon concentration and gradient layer at the joining interface, thereby improving bonding strength and wear resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025063345000001_ABST
    Figure 2025063345000001_ABST
Patent Text Reader

Abstract

To provide a steel material joined body and a manufacturing method thereof that improve the bending strength of mutual steel materials of a steel material joined body having different diameters at a joint surface.SOLUTION: In a steel material joined body 1, a plurality of mutual steel materials with different diameters at a joint surface are joined. In the steel material joined body, mutual central axes of the bonded steel materials coincide at the joint surface, and a carbon concentration of a joint interface of mutual steel materials is 0.20 mass% to 2.10 mass%. Further, the steel material joined body includes a concentration inclination layer in which the carbon concentration gradually decreases when separating from the joint interface.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a steel member joint and a manufacturing method thereof. [Background technology]

[0002] There is known a method for manufacturing a joined steel member in which the joining surfaces of steel members to be joined via a carbonaceous material are overlapped and heated (see Patent Documents 1 to 3). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Japanese Patent Application Publication No. 6-7970 [Patent Document 2] Japanese Patent Application Publication No. 57-22867 [Patent Document 3] JP 2023-39175 A Summary of the Invention [Problem to be solved by the invention]

[0004] However, the steel member joints obtained by the techniques described in Patent Documents 1 to 3 could not be said to have improved bending strength between steel members of a steel member joint having different diameters of the joint surface. Therefore, the present invention aims to provide a steel member joint capable of improving the bending strength between steel members of a steel member joint having different diameters of the joint surface. Another aim of the present invention is to provide a method for manufacturing a steel member joint capable of improving the bending strength between the steel members. [Means for solving the problem]

[0005] The steel material joint of the present invention is a steel material joint in which a plurality of steel materials having different diameters of a joint surface are joined together, the central axes of the joint surfaces of the joined steel materials are aligned, the carbon concentration at the joint interface between the steel materials is 0.20 mass% or more and 2.10 mass% or less, and the joint has a concentration gradient layer in which the carbon concentration decreases with increasing distance from the joint interface. The carbon concentration is preferably 0.20 mass % or more and 0.90 mass % or less.

[0006] The manufacturing method of a steel material joint according to the present invention is a manufacturing method of a steel material joint in which a plurality of steel materials having different diameters of a joining surface are joined together, and is characterized by comprising: a positioning step of positioning a carbonaceous material on at least one of the joining surfaces of the steel materials to be joined; a superposition step of overlapping the joining surfaces of the steel materials to be joined by aligning the central axes of the joining surfaces of the steel materials to be joined via the carbonaceous material; and a heating step of heating the steel materials with the overlapped joining surfaces at a maximum temperature of 1150°C or more and 1500°C or less. The carbonaceous material is preferably disposed only in the area of ​​the joining surface having a small diameter. Effect of the Invention

[0007] According to the present invention, it is possible to provide a steel member joint capable of improving the bending strength between steel members of a steel member joint having different diameters of the joining surface. Also, according to the present invention, it is possible to provide a manufacturing method for a steel member joint capable of improving the bending strength between the steel members. [Brief description of the drawings]

[0008] [Figure 1] FIG. 2 is a conceptual diagram for explaining a steel joint according to an embodiment of the present invention. [Diagram 2] FIG. 2 is a process flow diagram for explaining a method for manufacturing a steel joint according to an embodiment of the present invention. [Diagram 3] FIG. 2 is a conceptual diagram for explaining a method for manufacturing a steel joint according to a specific embodiment of the present invention. [Figure 4]FIG. 2 is a phase diagram of an iron-cementite system for explaining the effect of the present invention. [Diagram 5] 1 is a conceptual diagram for explaining the effect of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] Hereinafter, an embodiment of the present invention will be described with reference to the drawings. FIG. 1 is a conceptual diagram for explaining a steel member joint according to the present embodiment. In the steel joint 1 according to the present embodiment, as shown in Fig. 1, a plurality of steel materials 10 (diameter T1), 20 (diameter T2) having different diameters of the joint surface are joined together. The central axes α of the joint surfaces of the joined steel materials 10, 20 coincide with each other. The carbon concentration (carbon concentration A shown in Fig. 1) of the joint interface 40 where the plurality of steel materials 10, 20 (hereinafter also referred to as "materials") are joined together is 0.20 mass% or more and 2.10 mass% or less. Furthermore, the joint interface 40 has concentration gradient layers 15, 25 in which the carbon concentration decreases with increasing distance from the joint interface 40.

[0010] In the steel material joint 1 of this embodiment, the central axes α of the joint surfaces of the joined steel materials 10, 20 coincide with each other, so that the bending strength of the steel materials 10, 20 of the steel material joint having different diameters of the joint surfaces can be improved compared to a case where the central axes α do not coincide with each other. Furthermore, since the carbon concentration at the joint interface 40 is 0.20 mass% or more and 2.10 mass% or less, the joint strength between the steel materials 10, 20 can be effectively improved, and the wear resistance of the outer circumferential surface in the vicinity of the joint interface 40 (within the range in which the concentration gradient layers 15, 25 are formed) can also be improved.

[0011] Specifically, since the carbon concentration of the bonding interface 40 is 2.10 mass% or less, crystallization of the solidified structure at the bonding interface 40 is suppressed. Therefore, since crystallization of a hard and brittle solidified structure can be suppressed at the bonding interface 40, the bonding strength between the steel materials 10 and 20 can be effectively improved. Furthermore, since the carbon concentration of the bonding interface 40 is 0.20 mass% or more, the hardness of the bonding interface 40 can be increased. Therefore, the wear resistance of the outer circumferential surface near the bonding interface 40 can also be improved.

[0012] The carbon concentration is preferably 0.20 mass% or more and 0.90 mass% or less. By setting the carbon concentration of the joint interface 40 to 0.20 mass% or more and 0.90 mass% or less, the joint strength between the steel materials 10, 20 can be more effectively improved. Specifically, the precipitation of cementite at the austenite grain boundaries is suppressed by setting the carbon concentration at the joint interface 40 to 0.90 mass% or less. Therefore, since the precipitation of cementite at the hard and brittle austenite grain boundaries at the joint interface 40 can be suppressed, the joint strength between the steel materials 10 and 20 can be more effectively improved.

[0013] The carbon concentration at the joint interface 40 in the joined steel member 1 according to this embodiment can be measured by cutting the joined steel member 1 along the joint interface 40, polishing the cross section, and measuring the carbon concentration using an element distribution measuring device such as an electron probe microanalyzer (EPMA) or an energy dispersive X-ray analyzer (EDX). In the present invention, the carbon concentration at the joint interface 40 is calculated by averaging measurements taken at any five points on the polished cross section.

[0014] The joined steel body 1 according to this embodiment has the concentration gradient layers 15, 25 in which the carbon concentration decreases with increasing distance from the joint interface 40. Therefore, since the carbon concentration is high at the joint interface 40 (see carbon concentration A shown in FIG. 1), the joint strength between the steel materials 10, 20 can be effectively improved. Furthermore, since the carbon concentration (carbon concentration B in FIG. 1) on the side opposite the joint interface 40 (the side of the steel materials (materials 10, 20) before joining) in the concentration gradient layers 15, 25 is lower than that at the joint interface 40, the materials 10, 20 can exhibit "elongation." Therefore, the joined steel body 1 according to this embodiment can be suitably used in applications where "elongation" is required on the materials 10, 20 side.

[0015] As shown in FIG. 1, the concentration gradient layers 15 and 25 preferably have a carbon concentration that decreases continuously with increasing distance from the bonded interface 40 . In the present invention, the term "continuously decreasing" refers to the carbon concentration decreasing proportionally from the joint interface 40 toward the multiple steel materials (raw materials) 10, 20 as shown in FIG. Since the concentration gradient layers 15, 25 have such a decreasing tendency, in addition to the above-mentioned effects, the ductility and toughness at the joint interface 40 are also improved.

[0016] The carbon concentration of the concentration gradient layers 15, 25 in the steel joint 1 according to this embodiment can be measured by cutting the steel joint 1 along the joint interface 40, then further cutting it in a direction away from the surface of the cut joint interface 40 (towards the materials 10, 20), and then polishing the cross section cut in the direction away. The carbon concentration can be measured using an element distribution measuring device such as an electron probe microanalyzer (EPMA) or an energy dispersive X-ray analyzer (EDX).

[0017] In the present invention, the decreasing tendency of the concentration gradient layers 15, 25 can be measured by measuring the carbon concentration at any five points (10 points in total) on a straight line from the carbon concentration at the bonded interface 40 to the carbon concentration at the materials 10, 20 in each direction from the bonded interface 40 to the materials 10, 20 on a polished cross section in the separating direction using an element distribution measuring device as described above, and creating a graph as shown in FIG. 1 in which the carbon concentration is plotted against the distance, with the distance from the bonded interface 40 on the horizontal axis and the carbon concentration on the vertical axis.

[0018] In addition, although the joined steel member 1 according to this embodiment does not depend on the structural form of the joint interface 40, it is preferable that the joint interface 40 is composed of pearlite. This pearlite can be obtained by air-cooling or slow-cooling the joined steel member 1 in an austenite state. When the joined interface 40 is composed of pearlite, the tensile strength and bending strength are increased, so that the joint strength of the joined interface 40 can be improved more effectively. The structural form of the joint interface 40 can be confirmed by cutting the joined steel member 1 along the joint interface 40, polishing the cut cross section, and then performing nital etching on the polished cross section, and then observing the resultant cross section with an optical microscope.

[0019] It is preferable that the bond interface 40 does not have cementite at the austenite grain boundaries. If grain boundary cementite is present, it may become a starting point for cracks to easily occur during tension and bending. The above term "not present" does not mean that there is no grain boundary cementite at all, but means that the abundance ratio of grain boundary cementite at the bond interface 40 is less than 10%. Here, the abundance ratio of grain boundary cementite at the bond interface 40 is confirmed by subjecting the cross section to nital etching and then using a point counting method in accordance with JIS G0555 on the cross section.

[0020] Incidentally, in the steel joint 1 according to this embodiment, the material of the steel materials (materials) 10 and 20 to be joined is not particularly limited as long as it is any steel material and a metal that can be integrated with each other. In addition, the alloy elements other than carbon of the joint interface 40 and the multiple steel materials (materials) 10 and 20 before joining are not particularly limited, and for example, as specified in JIS G 4051, it has a composition that contains approximately 1.50 mass% or less of Si, 1.00 mass% or less of Mn, and the balance is Fe and unavoidable impurities. Furthermore, the shape of the multiple steel materials (materials) 10, 20 before joining is not particularly limited as long as they each have a central axis α and a joining surface, and can be integrated with each other by overlapping the central axes α of the joining surfaces so as to coincide with each other. The steel materials (materials) 10, 20 can be, for example, cylindrical, prismatic, screw-shaped, or uneven.

[0021] FIG. 2 is a process flow diagram for illustrating the method for manufacturing a steel joint according to the embodiment of the present invention. The method for manufacturing a steel member according to this embodiment is a method for manufacturing a steel member in which a plurality of steel members having different diameters of their joining surfaces are joined together, as shown in FIG. 2, and includes an arrangement step S101 of arranging a carbonaceous material on at least one of the joining surfaces of the steel members to be joined, a superposition step S102 of overlapping the joining surfaces of the steel members 10, 20 to be joined via the carbonaceous material by aligning the central axes of the joining surfaces of the steel members 10, 20 to be joined via the carbonaceous material, and a heating step S103 of heating the steel members with their joining surfaces overlapped at a maximum temperature of 1150°C or more and 1500°C or less.

[0022] In the manufacturing method of the joined steel member according to the present embodiment, as described above, the central axes of the joining surfaces are aligned with each other, overlapped, and heated. The term "aligning the central axes" used here can be achieved by aligning the axes by an operator or by a device for joining and heating in the manufacturing method of the joined steel member according to the present embodiment. As described above, in the steel material joint 1 manufactured in this embodiment, the central axes α of the joint surfaces of the joined steel materials 10, 20 having different joint surface diameters coincide with each other, and therefore the bending strength of the steel materials 10, 20 can be improved compared to those in which the central axes α do not coincide with each other.

[0023] Each of these steps will now be described in detail. 3 is a conceptual diagram for explaining a method for manufacturing a steel joint according to a specific embodiment of the present invention. In the manufacturing method of the steel joint 1 according to this embodiment, in the placement step S101, as shown in FIG. 3(a), a carbonaceous material 30 is placed on at least one of the joining surfaces (10a and / or 20a: in FIG. 3(a) it is the joining surface 20a with the smaller diameter) between the steel materials 10, 20 having different joining surface diameters. At this time, the carbonaceous material is preferably disposed so that a liquid phase L (described later in FIG. 4) is generated on the joining surfaces (10a and 20a) at the maximum temperature reached during heating in a heating step S103 described later. By arranging them in this manner, the joining strength between the steel materials can be improved more effectively.

[0024] Here, the material of the steel materials 10 and 20 to be joined, which have different diameters of the joining surface, is not particularly limited as long as it is a metal that can be integrated with each other, and can be any steel material. For example, low carbon steel, medium carbon steel, high carbon steel, etc. can be used. In the present invention, medium carbon steel refers to a steel material with a carbon concentration of 0.30 mass% or more and 0.50 mass% or less. Incidentally, low carbon steel refers to a steel material with a carbon concentration of less than 0.30 mass%, and high carbon steel refers to a steel material with a carbon concentration of more than 0.50 mass%. In addition, when low carbon steel, medium carbon steel, and high carbon steel are used, the alloy elements other than carbon are not particularly limited, but may be, for example, as specified in JIS G 4051, a composition consisting of approximately Si: 1.5 mass% or less, Mn: 1.0 mass% or less, and the balance Fe and unavoidable impurities.

[0025] The shape of the steel materials 10 and 20 having different diameters of the joining surfaces is not particularly limited as long as they have joining surfaces 10a and 20a, respectively, and can be integrated with each other by overlapping the joining surfaces 10a and 20a with the central axes α of the joining surfaces 10a and 20a aligned with each other. For example, a cylindrical shape, a prismatic shape, a screw shape, a concave-convex shape, etc. can be used (a cylindrical shape in FIG. 3). Furthermore, the carbonaceous material 30 can be placed on at least one of the joining surfaces (10a and / or 20a) of the steel materials 10, 20 to be joined, and the material and shape are not particularly limited as long as these joining surfaces 10a, 20a can be integrated. For example, a powdered carbonaceous material 30a or a sheet-like carbonaceous material 30b shown in Fig. 3 can be used. When using a powdered carbonaceous material 30a, it can be arranged by being applied to the joining surfaces (10a and / or 20a). When using a sheet-like carbonaceous material 30b, it can be directly arranged on the joining surfaces (10a and / or 20a).

[0026] The carbonaceous material is preferably disposed only in the area of ​​the joining surface having a small diameter. In other words, the carbonaceous material may be placed only within the range of the joining surface 10a with a larger diameter and the joining surface 20a with a smaller diameter where the central axes α are aligned and overlapped, or the carbonaceous material may be placed only within the range of the joining surface 20a with a smaller diameter. By arranging the material in this manner, the amount of carbonaceous material used can be reduced, and the steel materials can be joined together using a more optimal amount.

[0027] <About the overlapping step S102> In the manufacturing method of the steel joint 1 according to this embodiment, in the overlapping step S102, the steel materials 10, 20 to be joined are overlapped with their central axes α of the joining surfaces (10a and 20a) aligned with each other via the carbonaceous material 30 arranged in the arrangement step S101, as shown in FIG. 3(b). In this overlapping step S102, when overlapping the joint surfaces (10a and 20a) of the steel materials 10 and 20, it is preferable to fix the joint surfaces by applying a load in the direction of at least one of the other surfaces. In this manner, in the overlapping step of this embodiment, by applying a load to fix the joint surfaces (10a and 20a) of the steel materials 10 and 20 to each other, it is possible to increase the joining strength between the steel materials (10 and 20).

[0028] More specifically, in the manufacturing method of the steel joint 1 according to this embodiment, in the overlapping step S102, the steel materials 10, 20 to be joined are overlapped by simply pressing the joining surfaces (10a and 20a) of the steel materials 10, 20 to be joined together via the carbonaceous material 30 arranged in the arrangement step S101, as shown in Figure 3(b). In this overlapping step S102, when overlapping the steel materials 10, 20 by simply pressing their joining surfaces (10a and 20a) against each other, it is preferable to fix the joining surfaces to each other by their own weight. In the overlapping step of this embodiment, by fixing the joining surfaces (10a and 20a) of the steel materials 10, 20 to each other by applying a load by their own weight in this manner, the joining strength between the steel materials (10 and 20) can be increased.

[0029] In addition, in this overlapping step S102, when overlapping the steel materials 10, 20 by simply pressing their joint surfaces (10a and 20a) against each other, it is preferable to further apply a load (pressing load) to fix the joint surfaces together. In the overlapping step of this embodiment, by applying a load to fix the joint surfaces (10a and 20a) of the steel materials 10, 20 against each other in this way, it is possible to increase the joining strength between the steel materials (10 and 20). In addition, when applying such a pressing load, it is preferable because it allows the joint surfaces (10a and 20a) of the steel materials 10, 20 to be overlapped against each other in a horizontal direction (not shown) instead of in a vertical direction as shown in FIG. 3.

[0030] <About the heating step S103> In the manufacturing method of the joined steel product 1 according to the present embodiment, in the heating step S103, the steel materials 10, 20 whose joining surfaces (10a and 20a) have been overlapped with each other in the overlapping step S102 are heated as shown in Fig. 3(c). Here, the maximum temperature to which the steel materials 10, 20 are heated is within a range in which a liquid phase L is generated at the joining interface 40 (see Fig. 4, described later).

[0031] More specifically, in the manufacturing method of the joined steel product 1 according to this embodiment, in the heating step S103, the steel materials 10, 20 whose joining surfaces (10a and 20a) have been overlapped in the overlapping step S102 are simply pressed against each other, and the joining surfaces are heated while being fixed to each other by their own weight, as shown in Fig. 3(c). Here, the maximum temperature to which the steel materials 10, 20 are heated is preferably within a range in which a liquid phase L is generated at the joining interface 40 (see Fig. 4, described later). Moreover, the heating is preferably performed by simply pressing the overlapping steel materials 10, 20 with their joining surfaces (10a and 20a) against each other while applying a load (pressing load) to fix the joining surfaces together. In this way, by applying a load while heating the steel materials 10, 20 with their overlapping joining surfaces (10a and 20a) in order to fix them together, it is possible to increase the joining strength between the steel materials (10 and 20). In addition, when applying such a pressing load, it is preferable because it is possible to heat the joining surfaces (10a and 20a) of the steel materials 10, 20 in a horizontal direction (not shown) instead of in a vertical direction as shown in Fig. 3.

[0032] As described above, in the placing step S101, it is preferable that the mass of the carbonaceous material is adjusted and placed so that a liquid phase L is generated at the bonding interface 40 at the maximum temperature reached during heating in the heating step S103. Therefore, since such a carbonaceous material is disposed on the joining surface, the carbon concentration is increased at the joining interface 40. As a result, the tensile strength and bending strength of the joining interface 40 are increased, and it is possible to effectively increase the joining strength of the joining interface 40, i.e., the joining strength between the steel materials.

[0033] In order to adjust and arrange the mass of the carbonaceous material so that liquid phase L (see FIG. 4) is generated at the joining interface 50 at the maximum temperature reached when the carbonaceous material is heated, for example, steel materials 10 and 20, which are made of a material having the same shape and carbon concentration as the steel joint that will become the product, are used, the mass of the carbonaceous material to be arranged at the joining interface 40 is changed, and a heating joining test is performed for each of them at the same maximum temperature reached, and the joining rate described below is evaluated, whereby the appropriate mass of the carbonaceous material that generates liquid phase L can be determined.

[0034] The heating means in the heating step S103 is not particularly limited as long as it does not impair the effects of the present invention, and various heating methods can be used, such as high-frequency induction heating 100 using a conventionally known heating coil 50, a heating furnace other than high-frequency induction heating, laser heating, etc. The atmosphere during heating in the heating step S103 is not particularly limited. The atmosphere includes, for example, an oxidizing atmosphere (oxygen, air, etc.) and a non-oxidizing atmosphere (nitrogen, argon, etc.).

[0035] The heating step S102 of the present invention is preferably performed by high-frequency induction heating 100. Since the high-frequency induction heating 100 can accurately and rapidly heat to a desired temperature, the above-mentioned joined steel body 1 can be produced.

[0036] Then, in the heating step S103 of the present invention, when the liquid phase L generated at the joining interface 40 of the steel materials 10 and 20 disappears, the steel materials (10 and 20) are joined together (FIG. 3(d)). The cooling step (including rapid cooling) after the heating step S102 of the present invention is not particularly limited, and conventionally known gas cooling or spray cooling using a coolant such as a polymer can be adopted. More specifically, the cooling step (not shown) after the heating step S103 of the present invention is not particularly limited, and may be any of the conventionally known methods such as natural cooling, gas cooling, and spray cooling using a quenching coolant such as a polymer.

[0037] Each step of the present invention has been described above. Next, a specific example of the mechanism by which the joining strength of steel materials is increased by carrying out each step will be described with reference to the drawings. Fig. 4 is a phase diagram of an iron-cementite system for explaining the effect of the present invention. Fig. 5 is a conceptual diagram for explaining the effect of the present invention, specifically, a conceptual diagram showing the reaction occurring at the bonding interface. The manufacturing method of the steel joint 1 according to this embodiment involves placing the carbon powder (carbonaceous material) on at least one of the joining surfaces of steel materials having different diameters, with the mass adjusted so that liquid phase L is generated at the maximum temperature reached during heating, and then heating the steel materials, with the joining surfaces of the steel materials to be joined via this carbonaceous material overlapping each other, in a predetermined atmosphere (e.g., in the air) at a predetermined maximum temperature reached (see FIG. 5(a)).

[0038] From FIG. 4, the temperature at which the liquid phase L is generated at the joint interface between the steel material and the carbonaceous material is 1150°C or higher and 1500°C or lower. Specifically, when the maximum temperature near the joining surface between the steel materials reaches, for example, 1250°C, a liquid phase L with a carbon concentration of 3.5 mass% is generated at the interface between the steel material and the carbonaceous material (see the part indicated by the square in Figure 4). This liquid phase L increases until the carbonaceous material disappears (see Figure 5(b)).

[0039] At 1250°C, the carbon concentration at the interface between the "austenite γ" region and the "austenite γ + liquid L" region (see the part marked with a circle in Figure 4) is 1.6 mass%. Therefore, at 1250°C, most of the steel is a single phase of austenite γ. Incidentally, when the carbon content exceeds 1.6 mass%, two phases, austenite γ and liquid L, coexist. Carbon diffusion is extremely fast at 1250°C, and when held at this temperature, carbon diffuses at a high speed from the joint surface of the steel into the internal austenite γ. As a result, at the interface between the liquid L and austenite γ phases, the austenite γ side steals carbon from the liquid L side in an attempt to maintain the carbon concentration at 1.6 mass%, and the liquid L decreases in an attempt to maintain the carbon concentration at 3.5 mass% (see Figure 5(c)). The liquid phase L eventually disappears and the joining of the steel materials is completed (see Fig. 5(d)).

[0040] The effect of the present invention in the heating step (step S103) of the present invention has been explained at a maximum temperature of 1250°C. However, based on the phase diagram of the iron-cementite system in FIG. 4 and the examples described later, it is considered that the above-mentioned effect of the present invention can be obtained in a temperature range in which the "austenite phase γ" region and the "austenite phase γ + liquid phase L" region are formed (maximum temperature of 1150°C or higher and 1500°C or lower). As described above, the mass of the carbonaceous material is adjusted so that liquid phase L is generated on the joining surface, the carbonaceous material is arranged, and the steel materials with the joining surfaces overlapped are heated at a maximum temperature of 1150°C or higher and 1500°C or lower, thereby performing the joining.

[0041] The maximum temperature is preferably 1150° C. or more and 1300° C. or less. By setting the maximum temperature to 1300° C. or less, it is possible to efficiently cool a heating member (coil, etc.) for heating the steel material, and also to suppress deformation of the joined steel material itself due to heat. The maximum temperature in the heating step S103 can be measured by a platinum-rhodium thermocouple welded to the outer circumferential surface of the steel material (raw material) side within 2 mm from the joining surface 50 of the steel material to be joined.

[0042] The present invention will now be described in more detail with reference to examples and comparative examples, although the present invention is not limited to these examples in any way. EXAMPLES

[0043] In Example 1, a cylindrical steel material 10 (length X1: 150 mm, diameter φ: 15 mm (diameter of joining surface 10a: T1)) and a cylindrical steel material 20 (length X2: 150 mm, diameter φ: 8 mm (diameter of joining surface 20a: T2)) with a carbon content of 0.450 mass% (medium carbon steel) were prepared. These were then joined together to produce a steel joint as a test specimen, as shown by reference numeral 1 in FIG. 1. At this time, carbon powder (carbonaceous material) was placed on the joint surface (reference numeral 20a in FIG. 3) of the two steel materials with the smaller diameter, and the steel materials were overlapped so that the central axes of the joint surfaces of the steel materials to be joined via the carbonaceous material were aligned. Next, high-frequency induction heating was performed at a maximum temperature of 1250°C in an air atmosphere, and then the materials were slowly cooled. Here, the mass of the carbon powder placed on each joint surface of the two steel materials was adjusted so that a reaction could occur at the joint interface as shown in FIG. 4 and FIG. 5. In addition, the carbon concentration at the joint interface after high-frequency induction heating was adjusted to 0.50 mass% by controlling the heating maintenance time at the maximum temperature.

[0044] In the comparative example, a steel member was produced in the same manner as in Example 1, except that the steel members were not overlapped so that the central axes of the joining surfaces of the steel members joined via the carbonaceous material coincided with each other. The bending strength near the joint interface 40 of each of the steel joints of the examples and comparative examples was measured, and it was found that the steel joint of Example 1 had a higher bending strength than the steel joint of the comparative example. [Industrial Applicability]

[0045] According to the joined steel member and the method for producing the same of the present invention, it is possible to improve the bending strength between the steel members of the joined steel member having joining surfaces with different diameters. Therefore, the steel member joint according to the present invention (manufactured according to the present invention) can be suitably used in steel structures having different diameters. [Explanation of symbols]

[0046] 1 Steel joint 10 Steel (material) 10a Joint surface 15 Concentration gradient layer 20 Steel 20a Joint surface 25 Concentration gradient layer 30 Carbonaceous materials 30 Carbonaceous materials 40 Joint interface 100 High frequency induction heating S101 Placement process S102 Layering process S103 Heating process A Carbon concentration (joint interface) B Carbon concentration (opposite side of the concentration gradient layer from the bonding interface) X1 Length (steel) X2 Length (steel) T1 diameter (steel material) T2 diameter (steel material) γ Austenite phase L liquid phase

Claims

1. A steel material joint in which a plurality of steel materials having different diameters of a joint surface are joined together, The central axes of the joining surfaces of the joined steel materials are aligned with each other, The carbon concentration at the joint interface between the steel materials is 0.20 mass% or more and 2.10 mass% or less, A joint of steel members having a concentration gradient layer in which the carbon concentration decreases with increasing distance from the joint interface.

2. The joined steel member according to claim 1, wherein the carbon concentration is 0.20 mass% or more and 0.90 mass% or less.

3. A method for manufacturing a steel material joint in which a plurality of steel materials having different diameters of a joint surface are joined together, comprising the steps of: A disposing step of disposing a carbonaceous material on at least one joining surface of the steel materials to be joined; a lamination process in which the joining surfaces of the steel materials to be joined are overlapped with each other while aligning central axes of the joining surfaces of the steel materials to be joined via the carbonaceous material; and a heating step of heating the steel materials with the joining surfaces overlapped to a maximum temperature of 1150°C or more and 1500°C or less.

4. The method for producing a joint of steel members according to claim 3, wherein the carbonaceous material is disposed only in an area of ​​the joint surface having a small diameter.

Citation Information

Patent Citations

  • Diffusion brazing method of steel

    JP1982022867A

  • Hot joining method for steel

    JP1994007970A

  • Method for producing steel material conjugant

    JP2023039175A